Identification and molecular characterization of novel duck reoviruses in Henan Province, China - Peng, Zhifeng; Zhang, Han; Zhang, Xiaozhan; Wang, Haiyan; Liu, Zihan; Qiao, Hongxing; Lv, Yujin; Bian, Chuanzhou (Frontiers in Veterinary Science, 2023)
Novel Duck reovirus (NDRV) is an ongoing non-enveloped virus with ten double-stranded RNA genome segments that belong to the genus Orthoreovirus, in the family Reoviridae. NDRV-associated spleen swelling, and necrosis disease have caused considerable economic losses to the waterfowl industry worldwide. Since 2017, a significant number of NDRV outbreaks have emerged in China. Herein, we described two cases of duck spleen necrosis disease among ducklings on duck farms in Henan province, central China. Other potential causative agent, including Muscovy duck reovirus (MDRV), Duck hepatitis A virus type 1 (DHAV-1), Duck hepatitis A virus type 3 (DHAV-3), Newcastle disease virus (NDV), and Duck tembusu virus (DTMUV), were excluded by reverse transcription-polymerase chain reaction (RT-PCR), and two NDRV strains, HeNXX-1/2021 and HNJZ-2/2021, were isolated. Sequencing and phylogenetic analysis of the σC genes revealed that both newly identified NDRV isolates were closely related to DRV/SDHZ17/Shandong/2017. The results further showed that Chinese NDRVs had formed two distinct clades, with late 2017 as the turning point, suggesting that Chinese NDRVs have been evolving in different directions. This study identified and genetic characteristics of two NDRV strains in Henan province, China, indicating NDRVs have evolved in different directions in China. This study provides an insight into the ongoing emerged duck spleen necrosis disease and enriches our understanding of the genetic diversity and evolution of NDRVs.